Ohranitev sluha s hibridnim polževim vsadkom (elektroakustična stimulacija) - klinični primer - Rebol, Janez (Zdravniški vestnik, 2013)
Typical preoperative hearing loss of candidates for a hybrid cochlear implant ranges from mild to moderate hearing loss in the low frequencies (up to 500 Hz) and severe to profound hearingloss in the mid and high frequencies (above 1500 Hz). Usually, the patients have limited or no benefit from hearing aids and their word discrimination score is between 1060 %. These patients often do not use the hearing aids at all, because they do not hear well in the middle and high frequencies. This 8-year old boy presented with symetrical hearing loss, which was profound in middle and high frequencies and moderate in low frequencies. Because of that, his speech development was impaired. We inserted a hybrid cochlear implant with a hearing preservation electrode by a traumatic insertion technique through the round window and succeeded to preserve his residual hearing. He adapted well to the use of hearing aid and cochlear implant and significantly improved understanding of the high frequency words and sentences.
Keywords: elektroakustična stimulacija; izguba sluha; naglušnost; polžev vsadek; therapy; zdravljenje